Environmental Threats in American and Macedonian Dystopian Fiction - Maleska, Kalina (Respectus Philologicus, 2023)
Various environmental changes threaten local environments and the world at large. Some of these changes have visible immediate effects on people’s lives, as exemplified by the pollution in the Macedonian capital of Skopje, which for several years has ranked among the world’s most polluted cities. Additionally, global warming is estimated to have devastating consequences for all life on Earth. While American writers have increasingly incorporated discussion of climate change into their fiction, Macedonian literature has rarely delved into environmental issues. Therefore, this article aims to contribute by exploring specific environmental aspects in several previously unexplored Macedonian dystopian works by Branko Prlja, Ivan Šopov and Biljana Crvenkovska. These works are compared to the novel Forty Signs of Rain by the American writer Kim Stanly Robinson, analysing the approaches employed in addressing environmental threats. The comparative view, as well as placing all of these works in the context of existing factual information about climate change and pollution, indicates the cultural differences between the narratives, but also the common ground they share about possible responses that may be undertaken to tackle environmental problems.